Evidence‐Based Reviews: How Evidence‐Based Practices are Systematically Identified. Issue 1 (16th December 2019) - Cook, Bryan G.; Collins, Lauren W.; Cook, Sara Cothren; Cook, Lysandra
Abstract: Evidence‐based reviews are a type of systematic literature review used to identify evidence‐based practices. When conducting an evidence‐based review, researchers apply predetermined standards to identify evidence‐based practices—practices that have been shown to reliably improve an outcome for a population of learners, according to evidence from a body of rigorous, experimental studies. In this article, we describe evidence‐based reviews, provide an overview of one set of evidence standards used in special education, and describe important caveats and considerations related to evidence‐based reviews. We conclude with two examples of evidence‐based reviews in the field of learning disabilities. Our take‐home message is that evidence‐based reviews are a trustworthy approach for identifying generally effective instructional practices—but no practices, not even evidence‐based practices, are effective for all learners.